ХАРАКТЕРИСТИКИ РЕЗОНАНСНИХ СИСТЕМ ДЛЯ ОТРИМАННЯ ВИСОКОЇ НАПРУГИ НА НАВАНТАЖЕННІ ЄМНІСНОГО ТИПУ - Вінниченко , Д.В. (Інститут електродинаміки Національної академії наук України, 2024)
The work is devoted to the comparative analysis of currents in inverter circuits of transformerless resonant and transformer resonant and non-resonant systems of the same power for obtaining high voltage on a capacitive load. The purpose of the work is to determine the type of system characterized by the smallest average operating current of the inverter switches. The dependence of the currents in the circuits of the inverters on the parameters of the resonant circuits was obtained, the results of calculations according to which allow us to state that the use of a transformerless circuit to ensure the same power of systems for obtaining high voltage on a capacitive type load will allow to almost halve the average operating current in the inverter circuit. Simulation modeling of the processes in the studied schemes was carried out, which confirms the obtained theoretical results. The use of high-voltage transformerless resonant systems to obtain high voltage on a capacitive load will allow to halve the nominal and maximum permissible current characteristics of the power elements of the converters.